2013
DOI: 10.1038/ncomms3641
|View full text |Cite
|
Sign up to set email alerts
|

Separation of a functional deubiquitylating module from the SAGA complex by the proteasome regulatory particle

Abstract: Gene expression is an intricate process tightly linked from gene activation to the nuclear export of mRNA. Recent studies have indicated that the proteasome is essential for gene expression regulation. The proteasome regulatory particle binds to the SAGA complex and affects transcription in an ATP-dependent manner. Here we report that a specific interaction between the proteasomal ATPase, Rpt2p and Sgf73p of the SAGA complex leads to the dissociation of the H2Bub1-deubiquitylating module (herein designated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…In principal, SAGA may release subcomplexes to participate in diverse functions. It was recently shown in S. cerevisiae that the proteasome is capable of pulling the enzymatically active DUB module, including Sgf73, Sgf11, and Sus1, from SAGA, indicating that separation of SAGA may normally occur (Lim et al 2013). Further investigation into the modularity of SAGA and its implications for transcriptional regulation in vivo may aid in understanding how this complex might provide a sophisticated mechanism for chromatin modification and gene regulation.…”
Section: Loss Of Ataxin-7 Reduces H2b Ubiquitination Genes and Developmmentioning
confidence: 99%
“…In principal, SAGA may release subcomplexes to participate in diverse functions. It was recently shown in S. cerevisiae that the proteasome is capable of pulling the enzymatically active DUB module, including Sgf73, Sgf11, and Sus1, from SAGA, indicating that separation of SAGA may normally occur (Lim et al 2013). Further investigation into the modularity of SAGA and its implications for transcriptional regulation in vivo may aid in understanding how this complex might provide a sophisticated mechanism for chromatin modification and gene regulation.…”
Section: Loss Of Ataxin-7 Reduces H2b Ubiquitination Genes and Developmmentioning
confidence: 99%
“…Relevant to this issue, studies have already reported that the DUB module can interact with non-SAGA complexes. Under wild-type conditions in yeast, the proteasome chaperones interact with the Ubp8 and Sgf73 and separate them from SAGA (Lim et al 2013). The yeast DUB module subunit Sus1 is also present in the mRNA export complex TREX-2 (Rodriguez- Navarro et al 2004).…”
Section: Dub and Hat Module Subunits Control Expression Of A Subset Omentioning
confidence: 99%
“…Notably, the DUB module can disassociate from SAGA under some conditions and remain stable. In yeast, a functional DUB module can be separated from SAGA by the proteasome regulatory particle (Lim et al 2013). In Drosophila, loss of the Sgf73 homolog Ataxin-7 leads to disassociation of an enzymatically active DUB module (Mohan et al 2014).…”
mentioning
confidence: 99%
“…Similarly, USP22 was shown to be active in vitro only when interacting with all subunits of the DUB module, including ATXN7L3, and was found to be fully active in vivo only as part of the SAGA complex (Lang et al 2011;Armour et al 2013). Although it was recently shown that the proteasome regulatory particle can separate a DUB module from the yeast SAGA complex in vitro, such a free DUB module has no apparent effect on the regulation of H2Bub in vivo (Lim et al 2013). In agreement with a role for SAGA in gene transcribed regions, different studies using ChIP on candidate genes previously suggested the recruitment of different SAGA subunits in gene bodies (Govind et al 2007; Wyce et al 2007), and genome-wide ChIP analyses in S. pombe and Drosophila embryos localized Gcn5 or Ada2b in the transcribed regions of a subset of expressed genes (Johnsson et al 2009;Weake and Workman 2012).…”
Section: Saga Acts On a Very Large Fraction Of Eukaryotic Genomesmentioning
confidence: 99%